Offending patterns – alone or in a group – and severe conduct problems: secondary analysis of cross-sectional questionnaire data. Issue 1 (28th December 2020) - Gilbert, Emma; Padmore, Jane; Norman, Ian
Abstract : Purpose: This study aims to builds upon the hypothesis that "gang" offenders have greater mental health vulnerabilities than both the offender and the general population. This study aims to determine whether there is a difference between the mental health difficulties experienced by young people who may be committing offenses or who may be non-offenders while exploring the interplay of conduct disorder (CD). Design/methodology/approach: Secondary data analysis was conducted of a cross-sectional survey of 449 young people in two secondary schools and the data was compared to the scores on the strengths and difficulties questionnaire (SDQ). A diagnosis of CD was given to the respondents scoring "abnormal" for conduct on the SDQ and the findings were compared to the total difficulties score of those without a diagnosis of CD. Findings: Those committing offenses both alone and within a group setting had significantly higher scores across all domains of the SDQ, indicating the prevalence of inattention and hyperactivity, emotional problems, lower prosocial behaviors and peer problems over other offending groups. The total difficulties scores on the SDQ were significantly higher for the offending groups that had a diagnosis of CD. Originality/value: The results suggest that offending patterns are included within the screening for CD subtypes and support the need for further research into tailored interventions that involve multi-agency collaboration. This research offers a new approach to the identification of severe CD with callous and unemotional traits by examining offensive behavior.